Curcumin administration and the effects on psychological status and markers of inflammation and oxidative damage in patients with type 2 diabetes and coronary heart disease. (December 2020) - Shafabakhsh, Rana; Mobini, Moein; Raygan, Fariba; Aghadavod, Esmat; Ostadmohammadi, Vahidreza; Amirani, Elaheh; Mansournia, Mohammad Ali; Asemi, Zatollah
Summary: Introduction: This study assessed the effects of curcumin intake on psychological status, markers of inflammation and oxidative damage in patients with type 2 diabetes mellitus (T2DM) and coronary heart disease (CHD). Method: This randomized, double-blind, placebo-controlled trial was performed in 60 patients with T2DM and CHD, aged 45–85 years with 2- and 3-vessel CHD. Patients were randomized into two groups to receive either 1000 mg/day curcumin (n = 30) or placebo (n = 30) for 12 weeks. Using RT-PCR method, gene expression related to insulin metabolism and inflammatory markers on mononuclear cells from peripheral blood was evaluated. Result: Curcumin intake significantly decreased Pittsburgh Sleep Quality Index (PSQI) (β −1.27; 95% CI, −2.27, −0.31; P = 0.01) compared to the placebo group. Curcumin intake caused a significant reduction in malondialdehyde (MDA) (β −0.20 μmol/L; 95% CI, −0.36, −0.04; P = 0.01), significant increase in total antioxidant capacity (TAC) (β 75.82 mmol/L; 95% CI, 3.400, 148.25; P = 0.04) and glutathione (GSH) levels (β 63.48 μmol/L; 95% CI, 26.58, 100.37; P = 0.001) when compared with the placebo. Additionally, curcumin intake upregulated peroxisome proliferator-activated receptor gamma (PPAR-γ) (P = 0.01). Conclusion: Curcumin intake for 12 weeks in patients with T2DM and CHD had beneficial effects on PSQI, TAC, GSH, MDA values, and gene expression of PPAR-γ. This study was retrospectively registered in the Iranian website (www.irct.ir ) for registration of clinical trials (http://www.irct.ir : IRCT20170513033941N63).